Evaluating the Effects of Matched and Unmatched Stimuli on Nail Biting in Typically Developing Children. (May 2014) - Zawoyski, Andrea M.; Bosch, Amanda; Vollmer, Timothy R.; Walker, Stephen F.
We evaluated the effects of matched and unmatched stimuli on nail biting for three typically developing children and adolescents. Antecedent-based assessments identified conditions when subjects were most likely to engage in nail biting. Treatment included the noncontingent delivery of four types of highly preferred stimuli: items hypothesized to match the oral, the tactile, or both the oral and tactile stimulation inherent to nail biting, as well as items that did not involve oral or tactile stimulation. Results suggested that all forms of alternative stimulation decreased nail biting.